2001
DOI: 10.1093/toxsci/62.1.140
|View full text |Cite
|
Sign up to set email alerts
|

Polycystic Kidney Disease Induced in F1 Sprague-Dawley Rats Fed para-Nonylphenol in a Soy-Free, Casein-Containing Diet

Abstract: para-Nonylphenol (NP; CAS #84852-15-3), an alkylphenol with a 9-carbon olefin side chain, is widely used in the manufacture of nonionic surfactants, lubricant additives, polymer stabilizers, and antioxidants. Due to its wide commercial use and putative endocrine activity in humans and wildlife, the NTP elected to assess its effects on reproduction in multigenerational studies. To avoid known estrogenic activity of phytoestrogens in soy and alfalfa, a soy- and alfalfa-free, casein-containing diet was used in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
14
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 35 publications
2
14
0
Order By: Relevance
“…Fan et al observed that NP injected orally to pregnant rats induces alteration of reproductive developmental landmarks in their offspring. We observed the effects of NP not reported by Latendresse et al (2001). This is the first study reporting that exposure to NP at the high dose during embryo organogenesis period, from pregnancy day 14 to 19, results in reductions in reproductive landmarks in pups.…”
Section: Discussionsupporting
confidence: 51%
“…Fan et al observed that NP injected orally to pregnant rats induces alteration of reproductive developmental landmarks in their offspring. We observed the effects of NP not reported by Latendresse et al (2001). This is the first study reporting that exposure to NP at the high dose during embryo organogenesis period, from pregnancy day 14 to 19, results in reductions in reproductive landmarks in pups.…”
Section: Discussionsupporting
confidence: 51%
“…As mentioned before, PKD has been induced by diphenylamine 6 , nordihydroguaiaretic acid 7 , diphenylthiazole 8 , alloxan 9 , streptozocin 9 , ferric-nitrilotriacetate 9 and 2-amino-4,5-diphenylthiazole 10 in young and adult animals and para-nonylphenol 11 and tetrabromobisphenol A 12 in newborn animals. The histological changes induced in newborn rats by para-nonylphenol are characterized by numerous large cystic tubules, which develop mainly in the outer medulla and occasionally contain necrotic epithelial cells and neutrophils, and by patchy areas of chronic interstitial nephritis.…”
Section: Discussionmentioning
confidence: 67%
“…Similar counterparts are known in other animal species, such as mice, rats, rabbits, springboks, dogs and swine 4,5 . Many investigators have reported that PKDs can be induced by various chemicals, including diphenylamine 6 , nordihydroguaiaretic acid 7 , diphenylthiazole 8 , alloxan 9 , streptozotocin 9 , ferric-nitrilotriacetate 9 and 2-amino-4, 5-diphenylthiazole 10 in young and adult animals and para-nonylphenol 11 and tetrabromobisphenol A 12 in newborn animals. However, the mechanisms responsible for the formation of renal cysts by these compounds are not yet clearly understood, although it has been said that formation of renal cysts may be associated with cell proliferation, alteration of tubular basement membrane and Na/K ATPase localization and/or activity in the target site of the tubules.…”
Section: Introductionmentioning
confidence: 73%
“…To determine if endocrine active compounds as mentioned above have any myelotoxicity, the effects of these compounds on the function of bone marrow were evaluated. Studies on the behavior and general toxicity were also performed, and most of these effects have been reported Flynn et al, 2001;Latendresse et al, 2001;Guo et al, 2002;Weis et al, 2002;Ferguson et al, 2003;Karrow et al, 2004;White et al, 2004White et al, , 2005. Exposure of F 1 generation Sprague-Dawley rats to these chemicals was achieved through dams gestationally and lactationally, and through feeding from weaning on PND 22 to PND 64.…”
Section: Introductionmentioning
confidence: 99%